The influence of hospital services on patient satisfaction in OPDs: evidence from the transition to a digital system in South Punjab, Pakistan - Shahida Kanwel; Zhiqiang Ma; Mingxing Li; Abid Hussain; Naila Erum; Saif Ahmad (BMC, 2024)
Abstract Background Pakistani's health services delivery system has been rarely evaluated regarding patient satisfaction. This study examined the performance of the Pakistani health system from the perspective of doctor services (DS), digital payment system (DPS), nurses' services (NS), laboratory services (LS), pharmacy services (PHS), registration services (RS), physical services (environmentally and tangible) and doctor-patient communication (DPC) about patient satisfaction. A random sampling technique was adopted for data collection. Methodology The Social Science Statistical Package (SPSS), analysis of moment structures (AMOS), and structural equation modeling were used to analyze the data for reliability, validity, correlations, and descriptive findings. The 879 responses were used for study analysis. Results The study revealed that patient satisfaction was found to be significantly affected positively by LS, PHS, DS, NS, and DPS, while DPC, RS, and PF were impacted non-significantly. Consequently, there is a considerable communication gap in the doctor-patient interaction, and Pakistan's healthcare system is confronted with a shortage of physical infrastructure and challenges in the digital system. Conclusion Furthermore, the insufficient emphasis on registration services necessitates immediate action to improve the entire patient experience and satisfaction. Identifying these shortcomings has the potential to result in a healthcare system that is more efficient and focused on the needs of the patients.